2002
DOI: 10.3171/jns.2002.96.4.0736
|View full text |Cite
|
Sign up to set email alerts
|

Reversible ischemia around intracerebral hemorrhage: a single-photon emission computerized tomography study

Abstract: This is the first study in which it is documented that some of the perilesional hypoperfused tissue around human ICH regains its perfusion in the long term, leading the authors to suggest that there may be a penumbra in human ICH. Medical or surgical therapeutic interventions could increase the volume of perilesional brain that recovers after the initial insult. The results of this study therefore support the concept that intervention in ICH has the potential to reduce the ultimate neurological deficit and imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 31 publications
1
44
1
2
Order By: Relevance
“…There is direct experimental evidence of ischemic tissue surrounding the hematoma, 43,44 and radiologic support is also available. [45][46][47] On the other hand, several clinical studies have not demonstrated the presence of perihematomal penumbra. [48][49][50][51] This phenomenon seems to be present in some patients but not all.…”
Section: Pathophysiologymentioning
confidence: 99%
“…There is direct experimental evidence of ischemic tissue surrounding the hematoma, 43,44 and radiologic support is also available. [45][46][47] On the other hand, several clinical studies have not demonstrated the presence of perihematomal penumbra. [48][49][50][51] This phenomenon seems to be present in some patients but not all.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Various imaging techniques are employed to study ongoing secondary neuronal injury in the perihematomal region, including positron emission tomography (PET), single photon emission computed tomography (SPECT), MR perfusion, and CT [19,[38][39][40][41][42][43][44][45][46][47][48]. Specifically, the results of PET studies have not shown evidence of hypoxia or ischemia (i.e., normal oxygen extraction fraction and 18 F-fluoromisonidazole uptake) surrounding the intraparenchymal hemorrhage.…”
Section: New Imaging Techniquesmentioning
confidence: 99%
“…There is controversy whether secondary ischemia contributes to brain injury after SICH. 51,80,111,114,136 Cushing 29 believed that brain injury due to SICH was the result of local pressure compressing the microcirculation and causing ischemia around a hematoma. Astrup, et al, 5 proposed the term "ischemic penumbra" to describe brain with CBF values above a lower limit of membrane dysfunction and cell death, but below an upper limit corresponding to electrophysiological dysfunction.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%
“…80 In a small study in which positron emission tomography was used, no zone of tissue hypoxia or "ischemic penumbra" was identified. 51 Siddique and colleagues, 114 however, analyzed serial SPECT scans obtained in patients with SICH and identified perilesional hypoperfusion. They were also able to demonstrate that some of the ischemic perilesional brain recovered its perfusion in the long term.…”
Section: Pathophysiological Mechanismsmentioning
confidence: 99%